RISK OF RETURN CHARACTERISTICS OF ISLAMIC BANK FINANCING PORTFOLIO IN INDONESIA - Habibi, Zamzam; Rusgianto, Sulistya (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2021)
The study aims to investigate the risk of return characteristics of Islamic bank financing portfolios. A quantitative approach of value at risk is used to estimate return volatility of Islamic commercial banks and Islamic business units in Indonesia for the period of May 2014 to June 2020. The finding suggests proportion of equity-based financing tends to increase in contrast to decreasing of debt and lease-based financing. While rate of return for all financing types tends to decline, the return of equity-based financing experiences higher volatility than other two financing types. The main finding regarding the decrease in value at risk indicates Islamic banks able to reduce risk of financing portfolio. The finding implies Islamic banks should continue to improve the best-practice of risk management based on their past experience to anticipate future risk. As for the regulators, the finding may be used to develop early warning system to anticipate a systemic failure in Islamic banking industry. Further research is recommended to explore impact of market behavior on the risk of each type of financing.